Foreign Direct Investment Determinants and Their Impacts in Meta-Analysis Literature and Systematic Reviews - Kaukab, M. Elfan (LP3M Universitas Putra Bangsa, 2023)
Foreign Direct Investment (FDI) is an important field, yet only a few comprehensive reviews available on its current development. There are several meta-analysis studies and systematic literature reviews. However, none has summarized the findings in a unity. This study examines 31 meta-analysis articles and systematic literature reviews published in the last five years. Besides, it sums up the five-decades-spanned research. It also observes the FDI determinants, impacts, and research gaps. We lean to highlight future research’s crucial direction and discover what is present nowadays. We conclude that the development of FDI studies is vast in the coming years. Many things are explorable to uncover the phenomenon deeper.